Network-targeting combination therapy of leptomeningeal glioblastoma using multiple synthetic lethal strategies: a case report - Castro, Michael P.; Sipos, Bence; Biskup, Saskia; Kahn, Nina (Frontiers in Oncology, 2023)
Network targeting of disease-specific nodes represents a useful principle for designing combination cancer therapy. In this case of a patient with relapsed leptomeningeal glioblastoma, comprehensive molecular diagnosis led to the identification of a disease network characterized by multiple disease-specific synthetic lethal vulnerabilities involving DNA repair, REDOX homeostasis, and impaired autophagy which suggested a novel network-targeting combination therapy (NTCT). A treatment regimen consisting of lomustine, olaparib, digoxin, metformin, and high dose intravenous ascorbate was employed using the principle of intrapatient dose escalation to deliver the treatment with adequate safety measures to achieve a definitive clinical result.